High performance all-organic flexural piezo-FET and nanogenerator via nanoscale soft-interface strain modulation - Dhakras, Dipti; Gawli, Yogesh; Chhatre, Shraddha; Wadgaonkar, Prakash; Ogale, Satishchandra (Physical Chemistry Chemical Physics, 2014)
Flexural strain fields are encountered in a wide variety of situations and invite novel device designs for their effective use in sensing, actuating, as well as energy harvesting (nanogenerator) applications. In this work we demonstrate an interesting all-organic device design comprising an electrospun P(VDF-TrFE) fiber-mat built directly on a conducting PANI film, which is also grown on a flexible PET substrate, for flexural piezo-FET and nanogenerator applications. Orders of magnitude stronger modulation of electrical transport in PANI film is realized in this device as compared to the case of a similar device but with a uniform spin-coated P(VDF-TrFE) film. We find that in the flexural mode of operation, the interaction between the laterally modulated nanoscale strain field distributions created by the fibers and the applied coherent strain field strongly influences the carrier transport in PANI. The transport modulation is suggested to occur due to strain-induced conformational changes in P(VDF-TrFE) leading to changes in carrier localization-delocalization. We further show that the fiber-mat based device system also works as an efficient nanogenerator capable of delivering power for low power applications.